KEMAMPUAN MENULIS TEKS NEGOSIASI SISWA MAS KHULAFAUR RASYIDIN KUBU RAYA MELALUI MODEL DISCOVERY LEARNING - yanto, Ari (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
Writing negotiation texts is a creative process that aims to create a piece of writing that presents an exchange of opinions between two or more parties with the aim of reaching an agreement. Negotiation texts often involve a bargaining process to find a mutually beneficial solution. The aim of writing this classroom action research is to describe steps to improve students' abilities in writing negotiation texts in class X IIS B MA Khulafaur Rasyidin Kubu Raya through the Discovery learning learning model. The research results show that the use of the Discovery Learning model has a more positive change impact, namely it can improve student learning outcomes in writing negotiation texts. The increase in student learning completeness in cycle I was 10 students or 31.25% who completed. Furthermore, in cycle II, very satisfying results were obtained, namely 30 students or 93.75% managed to get the expected grades because they reached or even exceeded the KKM 77. Thus, the conclusion of this research is that there is an increase in student learning outcomes in writing negotiation texts. by applying the Discovery Learning learning model to class X IIS B MAS Khulafaur Rasyidin Kubu Raya students.